Primary headache epidemiology in children and adolescents: a systematic review and meta-analysis - Onofri, Agnese; Pensato, Umberto; Rosignoli, Chiara; Wells-Gatnik, William; Stanyer, Emily; Ornello, Raffaele; Chen, Hui Zhou; De Santis, Federico; Torrente, Angelo; Mikulenka, Petr; Monte, Gabriele; Marschollek, Karol; et al. (Journal of headache and pain, 2023)
Introduction Headache is the most prevalent neurological manifestation in adults and one of the leading causes of disability worldwide. In children and adolescents, headaches are arguably responsible for a remarkable impact on physical and psychological issues, yet high-quality evidence is scarce. Material and methods We searched cross-sectional and cohort studies in Embase, Medline, Web of Science, and Cochrane databases from January 1988 to June 2022 to identify the prevalence of headaches in 8–18 years old individuals. The risk of bias was examined with the Joanna Briggs Institute (JBI) scale. A random-effects model was used to estimate the pooled prevalence of pediatric headache. Subgroup analyses based on headache subtypes were also conducted. Results Out of 5,486 papers retrieved electronically, we identified 48 studies that fulfilled our inclusion criteria. The pooled prevalence of primary headaches was 11% for migraine overall [95%CI: 9–14%], 8% for migraine without aura (MwoA) [95%CI: 5–12%], 3% for migraine with aura (MwA) [95%CI:2–4%] and 17% for tension-type headache (TTH) [95% CI: 12–23%]. The pooled prevalence of overall primary headache in children and adolescents was 62% [95% CI: 53–70%], with prevalence in females and males of 38% [95% CI: 16–66%] and 27% [95% CI: 11–53%] respectively. After the removal of studies ranked as low-quality according to the JBI scale, prevalence rates were not substantially different. Epidemiological data on less common primary headaches, such as trigeminal autonomic cephalalgias, were lacking. Conclusion We found an overall remarkably high prevalence of primary headaches in children and adolescents, even if flawed by a high degree of heterogeneity. Further up-to-date studies are warranted to complete the picture of pediatric headache-related burden to enhance specific public interventions.